2021
DOI: 10.18203/2320-6012.ijrms20213078
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dry eye after radiotherapy for head and neck tumours: a tertiary Care Hospital North West Rajasthan

Abstract: Background: Radiotherapy plays a critical role in the management of many patients with head-and-neck (H&N) cancer. To study the incidence of dry eye associated with radiotherapy and correlate them with dose of radiation.Methods: This Hospital based prospective study comprises of 100 patients of head and neck tumors who received radiotherapy by linear accelerator from 2015 to 2017. Ocular examination was done prior to the start of therapy, 1st follow up at 15th day of therapy, 2nd at last day of therapy (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[ 14 ] and Jain et al . [ 21 ] Jiang et al . (1994) reported a 30% incidence of dry eye for doses >40 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] and Jain et al . [ 21 ] Jiang et al . (1994) reported a 30% incidence of dry eye for doses >40 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The study also suggested the importance of total dose as well as dose per fraction in causing DES in such patients. [12] Radiation also damages the limbal stem cells and can cause limbal ischemia in such patients leading to chronic non healing epithelial defect. In our study we found one patient who developed limbal ischemia.…”
Section: Discussionmentioning
confidence: 99%